SIMULTANEOUS ELECTIONS IN INDIA: CHALLENGES AND REMEDIES - Huggi (Desai), Saroja (International Journal of Psychosocial Rehabilitation, 2026)
This paper deals with the challenges that the Indian Election Commission has to face to synchronise the elections of both centre and the states. The positive benefit overrides the negative which could be resolved by some sacrifices, adjustments and some amendments to the existing rules in the constitution. It is of course difficult to hold simultaneous elections to the whole country as many state assemblies have different stage of their tenure. But this is not at all a new concept to be denied as well. The country has witnessed simultaneous elections immediately after implementation of our new constitution. Later on due to unavoidable situations country went on holding separate elections in different slots. This paper gives the idea that how we can succeed in implementation of simultaneous elections, what challenges are to be faced and the pros and cons of the scheme.